TiO2-Based Indium Phosphide Metal-Oxide-Semiconductor Capacitor with High Capacitance Density - Cheng, Chun-Hu; Hsu, Hsiao-Hsuan; Chou, Kun-I (My University, 2015)
We report a low-temperature InP p-MOS with a high capacitance density of 2.7 mu F/cm(2), low leakage current of 0.77 A/cm(2) at 1 V and tight current distribution. The high-density and low-leakage InP MOS was achieved by using high-kappa TiLaO dielectric and ultra-thin SiO2 buffer layer with a thickness of less than 0.5 nm. The obtained EOT can be aggressively scaled down to <1 nm through the use of stacked TiLaO/SiO2 dielectric, which has the potential for the future application of high mobility III-V CMOS devices.
Keywords: Indium Phosphide (InP); TiLaO; Equivalent Oxide Thickness (EOT)